A Study Examining Chest Injuries Caused by Blunt Trauma Through Prospective Autopsy Analysis (Medical Forum Monthly, 2023)
Objective: To screen plant extracts for their anti-cancer potential, considering their cost-effectiveness and low side effects. Further research is needed on animals and humans to apply it to cancer treatment in the future. Cancer is one of the leading causes of death in prosperous countries. This study evaluated the anti-cancer activity of the ethanolic extract of Grewia asiatica against the HepG2 cell line. The study aimed to check the cytotoxic effect of the extract on the cancer cell line, using different viability assays such as MTT, Crystal violet, Trypan blue, and Scratch assay.Study Design: Experimental studyPlace and Duration of Study: This study was conducted at the Institute of Molecular Biology and Biotechnology (IMBB), University of Lahore from July 2021 to Dec 2021.Methods: The cell and tissue culture test center at the University of Lahore will provide the HepG2 and normal cell lines. The cell lines that have been frozen in Liq. Nitrogen cylinders will be thawed from cryo vials when culturing is needed. The dried plant of Grewia asiatica will be obtained from the commercial market of Bahawalpur (The Islamia University Bahawalpur). The dried plant will be rinsed using tap water and dried in the shade.Results: The results indicated that the ethanolic plant extract showed a significant reduction in the level of proliferation of HepG2 cells compared to untreated cells.Conclusion: The ethanolic plant extract of Grewia asiatica has an effective in-vitro role in anti-cancer therapy. MTT assay estimated the reduction in the growth rate of rapidly dividing tumor cells, while the crystal violet and trypan blue assays showed that the plant extract elicited a significant inhibition of cell viability. The scratch assay also displayed the anti-cancer potential of the plant extract.